Recombinant Sj16 protein with novel activity alleviates hepatic granulomatous inflammation and fibrosis induced by Schistosoma japonicum associated with M2 macrophages in a mouse model - Jia Shen; Lifu Wang; Mei Peng; Zhen Liu; Beibei Zhang; Tao Zhou; Xi Sun; Zhongdao Wu (Parasites & Vectors, 2019)
Abstract Background Potent granulomatous inflammation responses induced by schistosome eggs and resultant fibrosis are the primary causes of morbidity in schistosomiasis. Recombinant Sj16 (rSj16), a 16-kDa protein of Schistosoma japonicum produced in Escherichia coli, has been demonstrated to have novel immunoregulatory effects in vivo and in vitro. Thus, this study investigated the anti-inflammatory and anti-fibrotic effects of rSj16 treatment in S. japonicum-infected mice and demonstrated the immune modulation between the schistosome and the host. Methods Schistosoma japonicum infected mice were treated with the rSj16 protein and Sj16 peptide at different time points post-infection to assess their efficacy at the optimal time point. Sj16 peptide and/or Praziquantel (PZQ) treatments were initiated at week 5 post-infection to compare the therapeutic efficacy of each regimen. Hepatic granulomatous inflammation, fibrosis and cytokine production (pro-inflammatory, Th1, Th2, Th17 and regulatory cytokines IL-10) were detected. Moreover, M2 macrophages were measured to illuminate the mechanisms of Sj16. Results The rSj16 protein and Sj16 peptide had significant protective effects in S. japonicum-infected mice, as shown by decreased granuloma formation, areas of collagen deposition and inhibition of pro-inflammatory Th1, Th2 and Th17 cytokine production. These protective activities were more obvious when animals were treated with either the Sj16 protein or peptide at early stages post-infection. Interestingly, the combined treatment of PZQ and Sj16 was more effective and upregulated IL-10 production than administration of PZQ alone in infected mice. Furthermore, the Sj16 treatment alleviated the pathological effects associated with activated M2 macrophages. Conclusions This study demonstrates the anti-inflammatory and anti-fibrotic effects of rSj16 in schistosomiasis. Therefore, the combination of rSj16 with PZQ could be a viable and promising therapeutic strategy for schistosomiasis. In addition, this investigation provides additional information on schistosome-mediated immune modulation and host-parasite interactions.